The New York Times and the U.S. presidential election 2012: framing same-sex marriage / Ahmad Azran Awang and Mokhtar Muhammad - Awang, Ahmad Azran; Muhammad, Mokhtar (CMIWS and UiTM Press, 2014)
Same-sex marriage is receiving further attention because the U.S. President Barack Obama has endorsed such marital partnership throughout his previous 2012 electoral campaign. Pragmatic nature of the media to set the agenda of the state causes same-sex marriage issue to receive immense news coverage by many America's news media ever since it becomes part of the Democratic Party electoral campaign, predominantly by the acclaimed "liberal" and "progay" newspaper, The New York Times.